Relasi Pendidik Dengan Peserta Didik di Era Millennial Dalam Pendidikan Islam - Muhamad Faizul Amirudin; Yesi Arikarani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
The problems that arise in this era are the first concerns about the replacement of educators with robotics or Artificial Intelligence (AI) when entering the era of the industrial revolution 4.0. Second, the development of various kinds of sophisticated technology has led to changes in attitudes and behavior between educators and students in the field of education, such as changes in communication ethics between the two, weakening respect and appreciation for educators. Third, educators are required to be adaptive to the development of modern technology and utilize it in practice in the world of education. This research is a literature review (library reaserch). The relationship between educators and students in the millennial era in Islamic education cannot be completely replaced by machines or robotics, because in the concept of Islamic education there is a planting of attitudes towards students which in this case requires the direct role of an educator.